2017
DOI: 10.1186/s13104-017-2535-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Toxoplasma gondii antibodies in patients with beta-hemoglobinopathies: the first report in the Americas

Abstract: BackgroundIn Brazil, there have been no previous studies of Toxoplasma gondii infection in sickle cell anemia patients and carriers of severe forms of beta-thalassemia. This study evaluated T. gondii infection in patients with beta-hemoglobinopathies.MethodsA total of 158 samples, 77 (48.7%) men and 81 (51.3%) women, were evaluated. Three groups were formed: G1 (85 patients with sickle cell disease); G2 (11 patients with homozygous beta-thalassemia; G3 (62 patients with heterozygous beta-thalassemia). ELISA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(55 reference statements)
0
3
2
Order By: Relevance
“…Also, our result was lower than those reported in different countries as Ghana [26], Cameroon [27] and Ethiopia [2833]. However, this seroprevalence of T. gondii antibodies was higher than that reported in European, North and West American continents [9, 34]. Such variations could be due to different study settings in terms of multiple climatic conditions, heterogeneous study population and risk factors profile such as contact with pets, hygienic practice, and feeding habit [28, 29, 31, 35, 36].…”
Section: Discussioncontrasting
confidence: 81%
“…Also, our result was lower than those reported in different countries as Ghana [26], Cameroon [27] and Ethiopia [2833]. However, this seroprevalence of T. gondii antibodies was higher than that reported in European, North and West American continents [9, 34]. Such variations could be due to different study settings in terms of multiple climatic conditions, heterogeneous study population and risk factors profile such as contact with pets, hygienic practice, and feeding habit [28, 29, 31, 35, 36].…”
Section: Discussioncontrasting
confidence: 81%
“…Also, our result was lower than those reported in different countries as Ghana (26), Cameroon (27) and Ethiopia (2833). However, this seroprevalence of T. gondii antibodies was higher than that reported in European, North and West American continents (9, 34). Such variations could be due to different study settings in terms of multiple climatic conditions, heterogenous study population and risk factors profile such as contact with pets, hygienic practice, and feeding habit (28, 29, 31, 35, 36).…”
Section: Discussioncontrasting
confidence: 75%
“…Infections pose a serious threat, and is reported to be the major cause of mortality and morbidity in thalassemic patients (Vento, Cainelli, and Cesario 2006). Although few studies have already reported the seroprevalence of Toxoplasma infection in β-hemoglobinopathies (Ferreira et al 2017)(El-Tantawy, Darwish, and Eissa 2019), no study has reported the possible association of HbF regulation with toxoplasmosis. In our study, we have identified the possible link of ZEB-AS1-has-miR-3646-ALOX5 axis with toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%